2018
DOI: 10.18512/1980-6477/rbms.v17n1p111-121
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Grãos E Forragem Em Função Da Disponibilidade Luminosa Em Sistema De Integração Lavoura-Pecuária-Floresta

Abstract: RESUMO - Neste trabalho, objetivou-se avaliar a produtividade da forragem e grãos de milho e do capim braquiária em consórcio, submetidos a diferentes níveis de sombreamentos proporcionados pelos renques de eucaliptos, em sistema de Integração Lavoura-Pecuária-Floresta, na região de Sete Lagoas-MG. O experimento foi conduzido na área experimental da Embrapa Milho e Sorgo, em Sete Lagoas-MG, em área de cultivo de eucalipto (Eucalyptus urophylla, clone AEC 1528) implantado em 29 de outubro de 2013, em espaçament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
1
1
0
1
Order By: Relevance
“…In spring and summer, PAR transmission was higher at iCLF_2 and iCLF_3 than at iCLF_1 and iCLF_4. PAR transmission values at iCLF_1 observed in this study were similar to that found by Prasad et al (2010) in an agroforestry system in India and by Pezzopane et al (2015) and Simão et al (2018) in Brazil. Table 3.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In spring and summer, PAR transmission was higher at iCLF_2 and iCLF_3 than at iCLF_1 and iCLF_4. PAR transmission values at iCLF_1 observed in this study were similar to that found by Prasad et al (2010) in an agroforestry system in India and by Pezzopane et al (2015) and Simão et al (2018) in Brazil. Table 3.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies in iCLF systems demonstrated the negative effect of adult trees on crop and pasture yields, mainly because of lower light availability for the understory plants and competition for water (Barro et al, 2008;Simão et al, 2018). Tree management practices in iCLF systems, such as pruning and thinning, reduce competition for light in these systems, at least for a short time (Nicodemo et al, 2016), which contribute to the proper productive balance between the system's components.…”
Section: Discussionmentioning
confidence: 99%
“…Os cultivos ocorrem na forma de consórcios entre culturas, em sistema de sucessão ou rotação. Busca-se obter, quando da aplicação desta estratégia, recuperação de áreas degradadas, viabilidade econômica e sustentabilidade ambiental, como resultantes das sinergias entre os distintos componentes do agroecossistema (BALBINO et al, 2011;BRASIL, 2013;SIMÃO et al, 2018). Quatro são as possíveis modalidades de aplicação dessa estratégia: i) o sistema Agropastoril ou Integração Lavoura-Pecuária (iLP), no qual ocorre a interação entre os componentes agrícola e pecuário, em sistema de rotação; ii) o sistema Agrossilvopastoril ou Lavoura-Pecuária-Floresta (iLPF), integrando os componentes agrícola, pecuário e florestal em sistema de rotação, consórcio e/ou sucessão, na mesma área; iii) o sistema Silvipastoril ou integração Pecuária-Floresta (iPF), em que os componentes pecuários (pastagem e animal) interagem com o componente florestal; e iv) o sistema Silviagrícola ou integração Lavoura-Floresta (iLF), no qual o sistema de 299 -Tecnologia de integração lavoura-pecuária-floresta (iLPF) produção integra os componentes florestal e agrícola pela consorciação de espécies arbóreas (BRASIL, 2013).…”
Section: Quadro Explicativounclassified